2015
DOI: 10.1016/j.jpeds.2014.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Occlusive Wrap for Heat Loss Prevention in Preterm Infants

Abstract: Application of occlusive wrap to very preterm infants immediately after birth results in greater mean body temperature but does not reduce mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 23 publications
2
69
0
5
Order By: Relevance
“…Preterm infants are especially vulnerable. Hypothermia is also associated with serious morbidities, such as increased risk of IVH, 19,26,39,[50][51][52][53][54] respiratory issues, 15,19,21,50,[55][56][57][58][59][60] hypoglycemia, 15,44,[60][61][62][63][64] and late-onset sepsis. 33,65 Because of this, admission temperature should be recorded as a predictor of outcomes as well as a quality indicator (Class I, LOE B-NR.)…”
Section: Importance Of Maintaining Normal Temperature In the Deliverymentioning
confidence: 99%
“…Preterm infants are especially vulnerable. Hypothermia is also associated with serious morbidities, such as increased risk of IVH, 19,26,39,[50][51][52][53][54] respiratory issues, 15,19,21,50,[55][56][57][58][59][60] hypoglycemia, 15,44,[60][61][62][63][64] and late-onset sepsis. 33,65 Because of this, admission temperature should be recorded as a predictor of outcomes as well as a quality indicator (Class I, LOE B-NR.)…”
Section: Importance Of Maintaining Normal Temperature In the Deliverymentioning
confidence: 99%
“…There is evidence of a dose effect on mortality, suggesting an increased risk of at least 28% for each 1°b elow 36.5°C body temperature at admission 42,43 and dose-dependent effect size. 42,43,48,66 One small randomized clinical trial 78 (very-low-quality evidence, downgraded for indirectness and serious imprecision) showed a reduction in adverse events, including death, intracranial hemorrhage, necrotizing enterocolitis, and oxygen dependence with improved temperature management, but 3 randomized controlled trials [79][80][81] (low-quality evidence, downgraded for indirectness and imprecision) did not show any significant improvement in mortality with significantly improved temperature control. Four observational studies 60,61,63,82 (very-low-quality evidence, downgraded for indirectness and imprecision) did not find any improvement in mortality with improved admission temperatures, but they were not sufficiently powered for this outcome.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…43,60,61,[88][89][90][91][92] For the important outcome of respiratory issues, there is evidence from 9 observational studies 44,48,50,67,83,[93][94][95][96] (low-quality evidence) showing an association between hypothermia and respiratory disease. One large randomized controlled trial 79 (low-quality evidence, downgraded for imprecision and risk of bias) found a reduction in pulmonary hemorrhage associated with improved admission temperature (OR, 0.57; 95% CI, 0.35-0.94). Eight observational studies (very-low-quality evidence) have shown an improvement in respiratory outcomes after improved admission temperature maintenance.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…There is evidence of a dose effect on mortality, suggesting an increased risk of at least 28% for each 1° below 36.5°C body temperature at admission 42,43 and dose-dependent effect size. 42,43,48,66 One small randomized clinical trial 78 (very-lowquality evidence, downgraded for indirectness and serious imprecision) showed a reduction in adverse events, including death, intracranial hemorrhage, necrotizing enterocolitis, and oxygen dependence with improved temperature management, but 3 randomized controlled trials [79][80][81] (low-quality evidence, downgraded for indirectness and imprecision) did not show any significant improvement in mortality with significantly improved temperature control. Four observational studies 60,61,63,82 (very-low-quality evidence, downgraded for indirectness and imprecision) did not find any improvement in mortality with improved admission temperatures, but they were not sufficiently powered for this outcome.…”
Section: Consensus On Sciencementioning
confidence: 99%